Second lockup period and post : IPO performance. - Ng, Si Min. (2009)
A lockup period is a predetermined amount of time following an initial public offering (IPO) during which insiders and pre-IPO shareholders are prohibited from selling their shares. In Singapore, it is a common practice for companies to have lockup periods, similar to firms in the United States. However, unlike in the United States, many firms in Singapore also have a second lockup period in underwriter agreement after the expiration of the first lockup period. During the second lockup period, insiders and pre-IPO shareholders are allowed to sell a portion of their shares, but they must ensure that their aggregate shareholdings do not fall below 50% of the company’s issued share capital.